MODALITY AND PERSUASION IN ADVERTISING: THE TRANSLATION ASPECT - Natalia I. Talan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The range of linguistic means and communication techniques used in advertising to influence the target group is extremely wide. The relevance of the study is in the growing interest of linguists to the problem of translation of advertising texts and slogans and the in the need of conducting of analysis of a significant number of existing translations. Advertising is a presentation of purposeful information about services and goods that has the character of persuasion. One of the most important aspects of advertising is the awakening in a potential audience of the desire to buy a product. Therefore, the vast majority of advertising must be convincing in nature in order to attract new buyers and customers to the product or idea. The purpose of our study is to analyze the features of the translation of advertising texts on the example of advertising of definite products. The following methods were used in the course of the work: 1) comparison, which allows the reader to establish the adequacy of word translation; 2) descriptive method used to show the successful translations and failures of translators. Speaking about the peculiarities of using the modality of persuasion in the advertising text, there are two ways to express it: 1) the imperative; 2) the use of statements with general motivational semantics, which is represented either in the lexical meanings of specific words, or at the level of general semantics of expression. Advertising performs several main functions, including the following ones: the central function – is the function of influence and also important communicative functions, which are divided into primary: communicative, regulatory and generalizing ones, and secondary: emotional, aesthetic, contact ones. In the group of advertising texts with the modality of persuasion, there are three subgroups: the selection criterion will be the form of expression of motivation and the role of this component in a particular ad. The attention should be paid to the advertising text in determining the role of a fragment often play a role not language but design tools, such as the location of blocks of information about each other, font size and shape, underlining, etc. All these factors help to understand which opinion is key for the author of the text. The persuasion can be defined as one of the most important ways of psychological advertising influence. The essence of this method is to convince the buyer of the benefits of the advertised product, to convince of the need to purchase it, it is aimed at the rational sphere of consciousness of the potential buyer, ie advertising appeals to his mind. Argumentation is a way of reasoning, in the process of which a benefit of the product is put forward as a thesis. And the need for an advertising thesis is proved by a system of arguments. Argument – is a separate piece of evidence that is part of the belief system, which proves the thesis. The most common method of addressing or advice is to save money or get a better service or product. The feeling that you are making a profitable purchase is a powerful means of motivation when you decide to buy something. This is such an effective method that price lists with inflated prices are often issued, and prices are much lower in advertising. In order to influence the recipient or in other words to implement the above-mentioned functions, the creators of advertising texts use various stylistic means of expression: phonetic (alliteration, onomatopoeia and rhyme), lexical (epithet, metaphor, personification, pun, hyperbole and allusion), syntactic (simple nominative propositions, parcelling, parallel constructions). Stylistic means add expressiveness to advertising, draw the recipient`s attention to the product, which is the main task of the advertising slogan.